Special crime investigation : with simulation on interview and interrogation - Garcia, Mario A. (Philippines : Wisemans Books Trading, Inc., 2020)
"This book delved into a wide range of topics in a conceptual presentation. It will not be difficult to use this book by simply comprehending and expanding your knowledge regarding the topics provided".
Includes bibliographical references.
English text.